2012
DOI: 10.3892/or.2012.2185
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine CXCL16 suppresses liver metastasis of colorectal cancer via augmentation of tumor-infiltrating natural killer T cells in a murine model

Abstract: Colorectal cancer (CRC) is a typical lifestyle-related disease, and it metastasizes mostly to the liver. It is important to understand the molecular mechanisms of CRC metastasis in order to design new and effective treatments for CRC patients. Chemokines are known to have antitumor effects as their chemoattractant properties stimulate the accumulation of infiltrating immune cells (TILs) in tumors. Chemokine (C-X-C motif) ligand 16 (CXCL16), also known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 41 publications
1
36
0
Order By: Relevance
“…Enhancement of humoral immunity and cellular immunity inhibition [2,40,47,76,77] Production of CCLl7, CCLl8, CCL22 Enhancement of adaptive immune response to Th2 type [2,76,77] Inhibition of Cdh1 gene and downregulation of E-cadherin expression Induction of epithelial-mesenchymal transition and promotion of tumor cells migration [78] TAM tumor-associated macrophage, VEGF vascular endothelial growth factor, CXCL C-X-C motif ligand, MMP matrix metalloproteinases Clin Transl Oncol promotion of CXCL16 expression may be a novel strategy for the treatment of metastatic CRC [48,49]. In addition, IL-1 secreted by TAMs can not only promote the proliferation of colon cancer cells through the GSK3 and Wnt signal pathway, but also directly block the apoptosis of tumor cells in the TRAIL pathway [50].…”
Section: Tams and Colorectal Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Enhancement of humoral immunity and cellular immunity inhibition [2,40,47,76,77] Production of CCLl7, CCLl8, CCL22 Enhancement of adaptive immune response to Th2 type [2,76,77] Inhibition of Cdh1 gene and downregulation of E-cadherin expression Induction of epithelial-mesenchymal transition and promotion of tumor cells migration [78] TAM tumor-associated macrophage, VEGF vascular endothelial growth factor, CXCL C-X-C motif ligand, MMP matrix metalloproteinases Clin Transl Oncol promotion of CXCL16 expression may be a novel strategy for the treatment of metastatic CRC [48,49]. In addition, IL-1 secreted by TAMs can not only promote the proliferation of colon cancer cells through the GSK3 and Wnt signal pathway, but also directly block the apoptosis of tumor cells in the TRAIL pathway [50].…”
Section: Tams and Colorectal Cancermentioning
confidence: 99%
“…Sites of [25][26][27] Gastric cancer TAM can promote angiogenesis reaction and the infiltration and metastasis of cancer cells. High expression of MIF and VEGF in tumor tissue hint that activation of TAM induces tumor angiogenesis [32][33][34] Breast cancer High expression of legumain by TAM is associated with significantly shorter survival time [44][45][46] Colorectal cancer The synergistic effect of CXCL16 and M1 can effectively inhibit colorectal liver metastasis [48,49] Lung cancer Bigger the ratio of the nest TAM and stromal TAM, more conducive to the survival of patients. M2 macrophages secrete IL-10 that induces CCR2 and CX3CR1 expression which can promote proliferation and/or migration [53][54][55] Esophageal carcinoma…”
Section: Tams and Gastric Cancermentioning
confidence: 99%
“…Similarly, high serum levels of sCXCL16 in colorectal cancer patients were associated with recurrent liver metastasis and poor prognosis (Matsushita et al , 2012). In contrast, in a murine model of colorectal cancer the expression of CXCL16 inhibited formation of liver metastases by recruitment of CXCR6 + T cells and NK cells (Kee et al , 2013). The latter data corroborate with the finding that CXCL16 expression in colorectal cancer patients associated with an increased number of CD4 + and CD8 + tumour infiltrating lymphocytes and a better prognosis (Hojo et al , 2007).…”
mentioning
confidence: 99%
“…Subsequently, it was shown that the defective tumor immunity observed in Jα18 -/- mice, selectively deficient for iNKT cells, against methylcholanthrene-induced sarcomas and melanoma lung metastasis could be restored by adoptive transfer of IFN-γ-producing iNKT cells from WT donor mice (Crowe et al, 2005). iNKT cells can be recruited to the tumor by inducing local expression of chemokines, such as CCL21 or CXCL16 (Turnquist et al, 2007; Kee et al, 2013) and be functionally activated by the alpha-galactosylceramide producing beneficial effects in a variety of solid tumors (Nakagawa et al, 2000; Osada et al, 2004; Nagato et al, 2012). iNKT cell infiltration in primary tumors has been correlated with a favorable outcome in patients with colorectal carcinoma (Tachibana et al, 2005), neuroblastoma (Metelitsa et al, 2004), and hepatocellular carcinoma (Guo et al, 2012a).…”
Section: Immune Cells Infiltrating the Tumor Microenvironment: Role Imentioning
confidence: 99%